2006
DOI: 10.1177/0020764006065146
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among Socioeconomic and Family Factors and Academic, Behavioral, and Emotional Difficulties in Filipino Adolescents in Hawai'i

Abstract: For Filipino adolescents (in both the whole and lower-SES samples), family support was an important protective factor against academic, behavioral and emotional difficulties. The role of cultural identification as a risk or protective factor among Filipino adolescents deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 22 publications
4
38
2
Order By: Relevance
“…Heras and Revilla (1994) wrote of the importance of family cohesion in individual adjustment among Filipino American youths, and Goebert et al (2000) found family support as a protective factor against psychopathology among multi-ethnic adolescents in Hawai'i. These findings are consistent with other research that has suggested that, for Filipino American adolescents in Hawai'i, family support is an important protective factor against academic, behavioral, and emotional difficulties, even for youth in lower socioeconomic groups (Guerrero et al, 2006). This article does not in any way intend to disparage Filipino Americans living in Hawai'i.…”
Section: Discussionsupporting
confidence: 91%
“…Heras and Revilla (1994) wrote of the importance of family cohesion in individual adjustment among Filipino American youths, and Goebert et al (2000) found family support as a protective factor against psychopathology among multi-ethnic adolescents in Hawai'i. These findings are consistent with other research that has suggested that, for Filipino American adolescents in Hawai'i, family support is an important protective factor against academic, behavioral, and emotional difficulties, even for youth in lower socioeconomic groups (Guerrero et al, 2006). This article does not in any way intend to disparage Filipino Americans living in Hawai'i.…”
Section: Discussionsupporting
confidence: 91%
“…57 Similarly, Guerrero et al found that speaking a language other than English protected against depression among Filipino adolescents in Hawaii. 86 Liu et al found that Chinese language proficiency was protective against depressive symptoms for foreign-born but not U.S.-born AA youth; additionally, youth proficient in Chinese who had mothers highly proficient in Chinese reported fewer depressive symptoms. 87 Juang and Cookston found that orientation to Chinese culture was associated with fewer depressive symptoms among Chinese adolescents.…”
Section: Question 4: What Protective Factors Exist To Buffer the Effementioning
confidence: 99%
“…Although research on the influence of ethnic identity on dating violence is still at its infancy, research suggests having a strong sense of ethnic identity may be a protective factor in other aspects of adolescent development. For example, Guerrero et al (2006) found that learning one's genealogy was positively correlated with school performance. In addition, Irwin et al (2005) found that having a clear sense of ethnic background and spending time trying to find out more about one's ethnic group and heritage are protective factors for delinquent and violent behavior for Asian and Pacific Islander youths.…”
Section: Discussionmentioning
confidence: 99%
“…Acculturation refers to the changes that groups or individuals experience when they are exposed to another culture (Williams & Berry, 1991). This may include changes in parental roles, as newer immigrant parents often work multiple low-waged jobs limiting their time to support and supervise their children who may be struggling to navigate through two cultures (Cheng & Ho, 2003;Guerrero, Hishinuma, Andrade, Nishimura, & Cunanan, 2006;Mayeda, Okamoto, & Mark, 2005). This is especially troubling in light of studies that suggest less parental supervision and involvement are associated with higher rates of dating violence (Chase et al, 2002;Magdol et al, 1998;Sanderson et al, 2004).…”
mentioning
confidence: 99%